Biofilm formation and antimicrobial susceptibility of non-diphtheriae corynebacterium strains isolated from blood cultures: First report from Turkey - Özdemir, Sinem; Aydoğan, Okan; Köksal Çakırlar, Fatma (Logos Medical Publishing, 2021)
Objective: Non-diphtheriae Corynebacterium strains have been recognized as important pathogens after decades of confusion regarding their microbiological classification and clinical significance. The aim of this study was to identify non-diphtheriae Corynebacterium strains and the prevalence of biofilm formation and antimicrobial resistance. Method: In total, 126 non-diphtheriae Corynebacterium strains were isolated from blood cultures of inpatients with bacteremia in our hospital between January 2015 and January 2020. Blood cultures were analyzed with the Bactec-9120 system. Strains were identified using MALDI-TOF MS (Bruker Daltonics, Germany). Antimicrobial susceptibilities were determined using the Kirby-Bauer disk diffusion method on a Mueller-Hinton agar and evaluated according to EUCAST standards. Biofilm formation was assessed with the Congo Red Agar method. Results: Corynebacterium striatum and Corynebacterium matruchotii were the most prevalent with 29 and 26 isolates, respectively. Biofilm production was detected in 62.06% (18/29) of C. striatum, in 53.8% (14/26) of C. matruchotii, in 50% (9/18) of Corynebacterium afermentans, 50% (6/12) of Corynebacterium amycolatum, and in 46% (7/15) of Corynebacterium jeikeium strains. Among the five most prevalent strains, we found a high biofilm rate of 54%. The resistance rates to penicillin, clindamycin, ciprofloxacin, rifampicin, tetracycline, and gentamicin were 91.2%, 87.3%, 79.3%, 56.3%, 45.2%, and 39.6%, respectively. All 126 strains were susceptible to vancomycin and linezolid. Conclusion: Non-diphtheriae Corynebacterium strains isolated from blood cultures of hospitalized patients with bacteremia may have multidrug resistance and the ability to produce biofilm. These results emphasize the importance of identifying strains and determining their antimicrobial susceptibility and biofilm production potential.

Amaç: Difteri-dışı Corynebacterium suşları, mikrobiyolojik sınıflandırmaları ve klinik önemi ile onlarca yıllık kafa karışıklığının ardından önemli patojenler olarak kabul edilmiştir. Bu çalışmanın amacı, difteri-dışı Corynebacterium suşlarının tür tayinin yapılması, biyofilm oluşumu ve antimikrobiyal direnç prevalansını araştırmaktır. Yöntem: Ocak 2015-Ocak 2020 tarihleri arasında hastanemizde yatarak tedavi gören bakteriyemili hastaların kan kültürlerinden difteri olmayan 126 Corynebacterium suşu izole edildi. Kan kültürleri Bactec-9120 sistemi ile analiz edildi. Suşların tanımlanması MALDI-TOF MS (Bruker Daltonics, Almanya) kullanılarak yapıldı. Antimikrobiyal duyarlılıklar Mueller-Hinton agarda Kirby-Bauer disk difüzyon yöntemiyle belirlendi ve EUCAST standartlarına göre değerlendirildi. Biyofilm oluşumu Congo Red Agar yöntemi ile değerlendirildi. Bulgular: Difteri-dışı Corynebacterium suşları arasında Corynebacterium striatum ve Corynebacterium matruchotii sırasıyla 29 ve 26 izolatla en yaygın suşlardı. Biyofilm üretimi C. striatum suşlarında %62,06 (18/29), C. matruchotii suşlarında %53,8 (14/26), Corynebacterium afermentans suşlarında %50 (9/18), Corynebacterium amycolatum suşlarında %50 (6/12) ve Corynebacterium jeikeium suşlarında %46 (7/15) olarak tespit edilmiştir. Çalışmanın en sık izole edilen ilk beş suşunda, %54 gibi yüksek bir biyofilm oranı bulduk. Penisilin, klindamisin, siprofloksasin, rifampisin, tetrasiklin ve gentamisine direnç oranları sırasıyla %91,2, %87,3, %79,3, %56,3, %45,2 ve %39,6 olarak tespit edildi. 126 suşun tamamı vankomisin ve linezolide duyarlıydı. Sonuç: Bu sonuçlar, hastanede yatan bakteriyemili hastaların kan kültürlerinden izole edilen Corynebacterium suşlarının biyofilm oluşturma yeteneğiyle birlikte çoklu-ilaç direnci gösterdiklerini ve kontaminasyon olarak göz ardı edilmemesi için, tür tayini ve antibiyotik duyarlılığının belirlenmesinin önemini vurgulamaktadır.
Kan kültürlerinden izole edilen difteri-dışı corynebacterium suşlarının biyofilm oluşturması ve antimikrobiyal duyarlılıkları: Türkiye’deki ilk bildirim
Keywords: Non-Diphtheriae Corynebacterium; Antimicrobial Susceptibility; Biofilm Formation; Corynebacterium Striatum; Corynebacterium Matruchotii; Corynebacterium Afermentans